2021
DOI: 10.1016/j.jece.2021.106872
|View full text |Cite
|
Sign up to set email alerts
|

Transforming agricultural waste into adsorbent: application of Fagopyrum esculentum wheat husks treated with H2SO4 to adsorption of the 2,4-D herbicide

Abstract: Wheat husks (Fagopyrum esculentum) were modified by treatment with sulfuric acid. The precursor material (FEWS) and the modified material (TFEWS) were characterized by different techniques to identify the structural changes promoted by the chemical treatment. Subsequently, TFEWS was applied as an adsorbent to remove the 2,4dichlorophenoxyacetic acid (2,4-D) pesticide from aqueous solutions. Adsorption studies considered the pH effects and adsorbent dosage on the sorption capacity. Also, it evaluated the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…When using peanut skin treated with H 2 SO 4 to remove an effluent containing 2,4-D and Atrazine, the authors observed removals of 15.01%, 46.0%, and 72.02% for the dosages of 1, 3, and 5 g L −1 , respectively [ 81 ]. In another study, residual husks of wheat Fagopyrum esculentum treated with H 2 SO 4 were used to treat samples of water from real rivers contaminated with 2.4-D [ 13 ]. This study observed the removal of around 76% for both analyzed rivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using peanut skin treated with H 2 SO 4 to remove an effluent containing 2,4-D and Atrazine, the authors observed removals of 15.01%, 46.0%, and 72.02% for the dosages of 1, 3, and 5 g L −1 , respectively [ 81 ]. In another study, residual husks of wheat Fagopyrum esculentum treated with H 2 SO 4 were used to treat samples of water from real rivers contaminated with 2.4-D [ 13 ]. This study observed the removal of around 76% for both analyzed rivers.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ]. In this sense, several materials have already been successfully applied in the removal of Diuron and other pesticides, such as wheat husk treated with H 2 SO 4 [ 13 ], corn cob [ 14 ], palm trunk [ 15 ], wood composites [ 16 ], mushroom residues [ 17 ], Physalis peruviana residues [ 18 ], bamboo stalk [ 19 ], the bark of the forest species Cedrella fissilis [ 20 ], araçá fruit bark [ 21 ], kaki seeds [ 22 ], leaves [ 23 ], baobab seed husks [ 4 , 24 ], bottom ash [ 25 ], and carbon nanotubes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they concluded that the alkaline-treated straw has biosorption properties suitable for sulphonylurea removal. In another recent study, sulphuric acid was used to treat wheat husks (Fagopyrum esculentum) for its modification and applied as adsorbent for the removal of 2,4-dichlorophenoxyacetic acid (2,4-D) pesticide from aqueous solutions (Franco et al 2021). Their findings showed that the maximum adsorption capacity attained was 161.1 mg/g at 298 K and electrostatic interactions was involved in adsorption mechanism.…”
Section: Herbicidesmentioning
confidence: 99%
“…In another work, wheat husks (Fagopyrum esculentum) modified using a treatment with H 2 SO 4 were applied as an adsorbent to remove the 2,4-D herbicide from water [49]. The kinetics, equilibrium, and thermodynamic behavior, as well as the pH effects and adsorbent dosage, on the adsorption capacity were investigated.…”
Section: Unmodified Modified Natural Materials and Ashesmentioning
confidence: 99%
“…According to the authors of papers [47][48][49], the oxidation of various biomass (Physalis peruviana fruit, Arachis hypogaea skins and wheat husks) with sulfuric acid resulted in oxygenated functionalities on their surface, which participated in the adsorption of the chlorophenoxy herbicides via electrostatic forces, hydrogen bonding, and van der Waals forces. The authors of the latter paper [49] also indicated halogen bonds and π-π interactions as responsible for adsorption. Noteworthy is the relatively high adsorption efficiency of acid-modified wheat husks, with the capacity of 161.1 mg g −1 (pH = 2, T = 298 K).…”
Section: Mechanism Of Adsorptionmentioning
confidence: 99%